Seismic vulnerability of non-structural members in reinforced concrete buildings located in Tehran - Aliasghar Amir Kardoust; Seyyed Azim Hosseini; Hamidreza Rabeifard; Seyyed Mohammad Seyyed Hosseini; Abbas Akbarpour NickghalbRashti (Numerical Methods in Civil Engineering)
Reinforced Concrete (RC) buildings are a common type of structure. Dual systems (containing RC shear walls and moment resisting frame), and moment resisting frame systems are the most common types of RC buildings in Iran. Some researchers have studied the seismic reliability of bridge structures using field data. However, in Iran, real field data is not used to analyze the reliability of RC buildings. In this study, reliability analysis is used to assess the failure of non-structural members in the RC buildings. The probability distribution of the concrete and steel bars strength is gathered by using field tests. The tests were done in 110 RC buildings in Tehran. Afterward, a series of time history analysis were done to determine the probability of failure in non-structural members. Monte Carlo sampling is used for reliability analysis. The reliability of two common RC structural systems are compared under different earthquake records. It is found that the dual system can have a better performance under seismic excitation and it can reduce the damage in an earthquake.